Prevalence and Incidence of Anal and Cervical High-Risk Human Papillomavirus (HPV) Types Covered by Current HPV Vaccines Among HIV-Infected Women in the SUN Study. (14th February 2018) - Kojic, Erna Milunka; Conley, Lois; Bush, Tim; Cu-Uvin, Susan; Unger, Elizabeth R; Henry, Keith; Hammer, John; Escota, Gerome; Darragh, Teresa M; Palefsky, Joel M; Brooks, John T; Patel, Pragna
Abstract : The prevalence of anal HR-HPV infection was higher than cervical and, for most HPV types, cleared more slowly. No differences were observed in incident HPV infections at the 2 anatomical areas or between 9-v and non-9-v HR-HPV. Abstract: Background: Nonavalent (9v) human papilloma virus vaccine targets high-risk human papillomavirus (HR-HPV) types 16, 18, 31, 33, 45, 52, 58, and low-risk 6, 11. We examined prevalence, incidence, and clearance of anal and cervical HR-HPV in HIV-infected women. Methods: The SUN Study enrolled 167 US women in 2004–2006. Anal and cervical specimens were collected annually for cytology and identification of 37 HPV types: 14 HR included: 9v 16, 18, 31, 33, 45, 52, 58; non-9v 35, 39, 51, 56, 59, 66, 68. Results: Baseline characteristics of 126 women included: median age 38 years; 57% non-Hispanic black; 67% HIV RNA < 400 copies/mL; 90% CD4 counts ≥200 cells/mm 3 . HPV prevalence at anus and cervix was 90% and 83%; for 9v HR-HPV types, 67% and 51%; non-9v HR-HPV, 54% and 29%, respectively. The 9v and non-9v HR-HPV incidence rates/100 person-years were similar (10.4 vs 9.5; 8.5 vs 8.3, respectively); 9v clearance rates were 42% and 61%; non-9v 46% and 59%, in anus and cervix, respectively. Conclusions: Anal HR-HPV prevalence was higher than cervical, with lower clearance; incidence was similar. Although prevalence of non-9v HR-HPV was substantial, 9v HR-HPV types were generally more prevalent. These findings support use of nonavalent vaccine in HIV-infected women.